Egzaltacja, czyli o uchylaniu granic - Burta, Małgorzata (Colloquia Litteraria, 2014)
Exultation, that is about gradual opening of the borders The article brings about an attempt to define exultation in the context of literary criticism from the period of the ‘aesthetic split’ (between late enlightenment and early romanticism currents) and pre-November heat of the 1830. It calls to attention the discussions in which Kazimierz Brodziński, the author of O egzaltacji i entuzjazmie [On Exultation and Enthusiasm], and his adversaries Maurycy Mochancki and Józefat Bolesław Ostrowski played crucial roles.